DESCRIPTION OF MIND-BODY-SPIRIT CONNECTION TO IMPROVE THE HOLISTIC WELL-BEING OF NURSING STUDENTS IN ONLINE LEARNING - Ismail, Suhartini (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: The COVID-19 pandemic has an impact on the education sector, especially for students and the academic community, and has an impact on the implementation of the online learning system. The existence of online learning has become a challenge for students to adapt, manage time, and manage self-management in learning. Less than optimal student adaptability can cause students' mind-body-spirit problems. The existence of physical, mental, and mental problems in students while adapting to online learning requires a balance of mind-body-spirit in their lives. The purpose of this study was to describe the mind-body-spirit connection to improve the holistic well-being of nursing students in online learning. Method: The research method uses a descriptive survey. The research sample was taken using a total sampling technique. Respondents in the study were undergraduate and postgraduate students in Nursing Science, Faculty of Medicine, Universitas Diponegoro, year of 2020 and 2021, with a total of 395 students. The Holistic Well-being Scale (HWS) questionnaire was used to collect data. Result: The results of this study found that the average measurement of the mind-body-spirit connection picture of nursing students in online learning was 189.94, which was interpreted in the sufficient category. Nursing students still need to improve their well-being through fulfilling the right aspects of mind, body, and spirit. Conclusion: -